Comparing the Effectiveness of Cognitive Behavioral Therapy, Dialectical Behavior Therapy, and Paradoxical Exposure Therapy on Distress Tolerance and Relational Distress in Dental Students with Histrionic Personality Traits - Nikbakht, Ghazaleh; Atashpour, Seyed Hamid; Torkan, Hajar (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: This study aimed to compare the effectiveness of cognitive behavioral therapy, dialectical behavior therapy, and paradoxical exposure therapy in improving distress tolerance and reducing relational distress among dental students with histrionic personality traits. Methods and Materials: This quasi-experimental study employed a four-group pretest–posttest design with a follow-up assessment. The statistical population consisted of dental students with histrionic personality traits attending hospital-based centers in Isfahan, Iran, during autumn 2024. Through convenience sampling and screening using the Millon Clinical Multiaxial Inventory–IV, 60 eligible students were selected and randomly assigned to cognitive behavioral therapy, dialectical behavior therapy, paradoxical exposure therapy, or a control group, with 15 participants in each group. Data were collected using the Distress Tolerance Scale developed by Simons and Gaher (2005) and the Inventory of Interpersonal Problems developed by Barkham et al. (1996). The data were analyzed using repeated-measures statistical procedures and post hoc comparisons in SPSS version 27. Findings: The effects of time, group, and the time-by-group interaction were statistically significant for both distress tolerance and relational distress (p < .01). Post hoc comparisons demonstrated significant differences between the control group and each of the three intervention groups in both outcome variables (p < .01). All three treatments significantly increased distress tolerance and reduced relational distress from pretest to posttest and follow-up. Dialectical behavior therapy produced the greatest improvement in distress tolerance and the largest reduction in relational distress compared with the other interventions. Cognitive behavioral therapy yielded the smallest change in distress tolerance, whereas paradoxical exposure therapy produced the smallest change in relational distress. Conclusion: Cognitive behavioral therapy, dialectical behavior therapy, and paradoxical exposure therapy are effective interventions for improving distress tolerance and reducing relational distress in dental students with histrionic personality traits; however, dialectical behavior therapy appears to have comparatively greater therapeutic effectiveness.